Effects of Semantic Richness on Lexical Processing in Monolinguals and Bilinguals - Taler, Vanessa; López Zunini, Rocío; Kousaie, Shanna (Frontiers in Human Neuroscience, 2016)
The effect of number of senses (NoS), a measure of semantic richness, was examined in monolingual English speakers (n=17) and bilingual speakers of English and French (n=18). Participants completed lexical decision tasks while EEG was recorded: monolinguals completed the task in English only, and bilinguals completed two lexical decision tasks, one in English and one in French. Effects of NoS were observed in both participant groups, with shorter response times and reduced N400 amplitudes to high relative to low NoS items. These effects were stronger in monolinguals than in bilinguals. Moreover, we found dissociations across languages in bilinguals, with stronger behavioral NoS effects in English and stronger event-related potential (ERP) NoS effects in French. This finding suggests that different aspects of linguistic performance may be stronger in each of a bilingual’s two languages.